Revaluation and reform of council tax in Wales: Impacts on different councils and household types - Stuart Adam; Louis Hodge; David Phillips; Xiaowei Xu (Institute for Fiscal Studies (IFS), 2020)
Council tax bands in Wales are based on property values in April 2003 - 17 years ago. That is more up to date than in England and Scotland, where they are based on values in April 1991 (almost 30 years ago!). But it is still enough time for the relative values of different properties to change significantly: for example, official estimates suggest that while average prices had doubled since 2003 across Wales as a whole by the end of 2019, those in Blaenau Gwent had risen 171% compared with just 77% in Wrexham. Moreover, while the difference in 2003 values between a property in Band A and a property in Band I was at least 9.5-fold, the difference in tax rates is just 3.5-fold. The structure of council tax is therefore both increasingly out of date and arbitrary, and highly regressive with respect to property values. It is ripe for revaluation and reform. This report examines how revaluation and reform of council tax in Wales would affect the tax bases, average net tax bills and grant funding requirements of different local authorities (LAs); and the net tax bills and after-tax incomes of different household groups. This is in the context of a commitment from the Welsh Government to make council tax fairer and more progressive.
Keywords: 330; Gemeindesteuer; Grundsteuer; Steuerreform; Steuerwirkung; Wales